Micro-ethnography: Towards An Approach for Attending to the Multimodality of Leadership. Issue 3 (3rd July 2022) - Alvehus, Johan; Crevani, Lucia
ABSTRACT : This paper addresses the need for further developing an understanding of leadership as practice in its multimodality by means of theoretically motivated qualitative methods, allowing researchers to come close to the doing of leadership. Empirical studies of this kind are still relatively rare. By articulating a micro-ethnographic approach, we encourage short-term-focused engagements in empirical work and the writing of closed vignettes. Through this, current theoretical developments are connected to recommendations for fieldwork and for writing practices. We thereby articulate one possible coherent and consistent position from which to study the multimodality of leadership and to understand leadership as an accomplishment of direction.